2017
DOI: 10.3390/nu9101148
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet with a High Monounsaturated Fatty Acid and Polyunsaturated/Saturated Fatty Acid Ratio Suppresses Body Fat Accumulation and Weight Gain in Obese Hamsters

Abstract: The aim of this study was to investigate the effect of a high fat diet with experimental oil consisting of 60% MUFAs (monounsaturated fatty acids) with a P/S ratio of 5 on fat deposition and lipid metabolism in obese hamsters. Hamsters were randomly assigned to a control group and a diet-induced obesity group for nine weeks. Then an additional eight-week experimental period began, during which obese hamsters were randomly divided into three groups and fed different amounts of the experimental oil mixture in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 56 publications
(61 reference statements)
4
24
0
Order By: Relevance
“…Slight increase in the level of triglyceride has been shown in rats fed with 15% sunflower oil as compared to rats fed with niger seed oil. This result agreed with the finding of a study that reported that increasing the polyunsaturated fatty acid content in food increases the Triacylglycerol level [ 35 , 36 ]. The levels of total cholesterol, HDL-c, LDL-c, and TAG were significantly ( p < 0.05) higher in rats fed with 15% palm oil compared to control group, rats fed with 15% niger seed oil, and rats fed with 15% sunflower oil.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Slight increase in the level of triglyceride has been shown in rats fed with 15% sunflower oil as compared to rats fed with niger seed oil. This result agreed with the finding of a study that reported that increasing the polyunsaturated fatty acid content in food increases the Triacylglycerol level [ 35 , 36 ]. The levels of total cholesterol, HDL-c, LDL-c, and TAG were significantly ( p < 0.05) higher in rats fed with 15% palm oil compared to control group, rats fed with 15% niger seed oil, and rats fed with 15% sunflower oil.…”
Section: Discussionsupporting
confidence: 93%
“…The significant decrease in body weight gain percentage of rats fed with 15% sunflower oil as compared to rats fed with 15% niger seed oil, rats fed with 15% palm oil, and control group and the significant ( p < 0.05) decrease in body weight gain percentage of rats fed with 15% niger seed oil compared with rats fed with 15% palm oil might be because of the fatty acid composition difference of sunflower oil, niger seed oil, and palm oil [ 28 32 ]. Researchers indicated that the utilization of polyunsaturated fatty acids increases the utilization of proteins and cholesterol and might assist in losing weight [ 35 , 36 ]. Research done on dietary fatty acid with utilization of polyunsaturated fatty acids reported that the polyunsaturated fatty acids facilitated the lipid metabolism and resulted in decrease in obesity [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we only used a single source of protein, yet some studies suggest that adiposity may depend on an interaction between protein source and high dietary fat content (McManus et al, 2015). We only used a single combination of saturated, monounsaturated, and poly-unsaturated fats, and again variation in these components has also been suggested to be important for weight gain (Yang et al, 2017;Piers et al, 2003;Liao et al, 2010). Finally, we used only one type of refined carbohydrate (sucrose) and delivered this in the food.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…The M/S ratio of this study is slightly higher. Diets with high M/S ratio of >1 decrease plasma HDL-C and triacylglycerides (Yang, Lin, Chang, & Chien, 2017). Sinanoglou, Batrinou, Mantis, Bizelis, & Miniadis-meimaroglou (2013) and Calder (2015) suggested that MUFA are heart protective while SFA may increase risk of cardiovascular disease.…”
Section: Lipid Health Indices For Groundnut Oilmentioning
confidence: 99%